A66 GEOGRAPHIC VARIATION AND INCREASED INVOLVEMENT OF INTERVENTIONAL RADIOLOGISTS IN THE MANAGEMENT OF REFRACTORY ASCITES: A POPULATION BASED STUDY. (26th February 2020) - Motomura, D; Djerboua, M; Flemming, J
Abstract: Background: The disease burden from cirrhosis is increasing worldwide. Refractory ascites (RA) is a complication of cirrhosis associated with poor prognosis if liver transplant is not an option. Serial large volume paracentesis (LVP) is the standard of care in the management of refractory ascites (RA) and outpatient LVP has been shown to be safe and cost effective. Epidemiologic data is lacking regarding the incidence of RA, or how patients with RA are managed in routine clinical practice. Aims: To describe secular trends in the incidence of RA in Ontario from 2000–2017, and to describe physician provider types performing LVPs in the RA population in Ontario. Methods: This retrospective, population-based cohort study uses routinely collected healthcare data from Ontario, Canada, housed at ICES. From January 1, 2000 to Dec 31, 2017 all adult patients with cirrhosis were identified using a validated case definition, and those with RA were identified based on the need for serial LVP. All LVP procedures were described based on patient demographics, local health integration network (LHIN), physician type (Gastroenterology [GI], Internal Medicine [IM], Interventional Radiology [IR], Emergency Medicine [ER], other) and albumin administration. Annual incidence rates (IR) of RA in patients with cirrhosis were calculated and compared using Poisson regression to calculate incident rate ratios (IRRs). Annual LVP volume by provider type and LHIN were calculated and differences were compared using chi-squared analysis. Results: The overall incidence of RA in patients with cirrhosis remained relatively stable over the study period (IRR 1.01, 95% CI 1.00–1.02 P<.001). The highest incidence of RA was in those with viral hepatitis and alcohol-related cirrhosis. A total of 90, 126 LVPs were identified (median age 61 years [IQR 53–70], 69% male, median LVP per patient 24 [IQR 11–48], 15.8% received albumin infusion). The absolute numbers of LVPs more than tripled over the study period (12, 047 in 1997–2002 vs. 37, 437 in 2013–2017). GI performed the majority of LVPs (40.1%) followed by IR (22.4%), and IM (8.4%), but there was substantial variation based on location (Fig 1). Overall, the proportion performed by IR increased during the study (7.8% in 1997–2002 vs 30.8% in 2013–2017, P <.001) while the proportion performed by GI decreased (50% 1997–2002 vs 33.1% 2013–2017, P<.001). Conclusions: The number of LVPs performed for RA have increased dramatically in Ontario over the past two decades, with the proportion being performed by GI physicians decreasing, while IR is increasing. Substantial variability exists across LHINs on the use of LVP, which may reflect differences in access to resources for LVP, or physician practice. Appropriate albumin use with LVP remains an area for potential quality improvement initiatives in the future. Funding Agencies: AASLD Foundation Clinical Translational and Outcomes Research Award in Liver Disease (for supervisor JF)